1983
DOI: 10.1159/000145802
|View full text |Cite
|
Sign up to set email alerts
|

Thin-Section, Tracer, and Freeze-Fracture Study of the Smooth-Ended Maturation Ameloblasts in Rat Incisors

Abstract: The morphology and functional roles of the smooth-ended maturation ameloblasts (SAs) of rat incisors were examined by means of routine thin sections, tracer experiments, and freeze-fracture replication. SAs possessed two sets of junctional complexes consisting of tight junctions (fasiae occludentes) and gap junctions at the proximal and distal ends. Neither the proximal nor the distal junctional complex formed a complete barrier around the cell; intravenously injected horseradish peroxidase (HRP) reached the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Areas of dissolution appeared as shallow, belt-like grooves (from 20 to 100 pLm wide) running horizontally around the enamel surface parallel to the cervical line of the crown in pre-molar and molar teeth, and transversely across the enamel surface in canine teeth. Two or three grooves of EDTA-etched enamel separated The distal cell surfaces show many micropores, which are thought to correspond to micropinocytotic pits (Sasaki et al, 1983b). [ x 6700] by undissolved enamel were usually observed on maturing enamel surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas of dissolution appeared as shallow, belt-like grooves (from 20 to 100 pLm wide) running horizontally around the enamel surface parallel to the cervical line of the crown in pre-molar and molar teeth, and transversely across the enamel surface in canine teeth. Two or three grooves of EDTA-etched enamel separated The distal cell surfaces show many micropores, which are thought to correspond to micropinocytotic pits (Sasaki et al, 1983b). [ x 6700] by undissolved enamel were usually observed on maturing enamel surfaces (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental studies have shown that, in rat incisors, the SA layer is highly permeable to tracers such as peroxidase and lanthanum and must allow access to EDTA (Kallenbach, 1980;Takano and Ozawa, 1980;Reith et al, 1982;Sasaki et al, 1983b;Josephsen, 1984). EDTA dissolution marks on maturing enamel surfaces of kitten permanent teeth seem to be similar to GBHA-positive stripes on the enamel of the bovine molar and the monkey incisor (Takano et al, 1982b) and to tetracycline labeling patterns on maturing enamel surfaces of kitten deciduous canine and molar teeth (Boyde and Reith, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In RAs, the distal TJ is a zonula occludens but the proximal TJ is a macula occludens (Sasaki et al, 1983a(Sasaki et al, , 1990. In SAs, the proximal TJ is a structurally incomplete zonula occludens but the distal TJ is a macula occludens (Sasaki et al, 1983b(Sasaki et al, , 1990.…”
mentioning
confidence: 99%
“…A well developed zonula occludens junction, made up of about ten rows of tight junctional strands, is present on the distal end of RA and on the proximal end of SA (Sasaki and Garant, in press). On the other hand, a permeable intercellular space is present at the proximal end of the RA and the distal end of the SA (Josephsen and Fejerskov, 1977;Kallenbach, 1980s;Sasaki et al, 1983;Sasaki and Garant, in press).…”
Section: Fig 8 the Distal Portion Of Transition Ameloblasts In The mentioning
confidence: 99%
“…A bidirectional exchange of substances is thought to occur along this pathway. Intravenously injected tracers such as horseradish peroxidase have been shown to gain access to the enamel at the location of the SAs (Kallenbach, 1980a;Takano and Ozawa, 1980;Sasaki et al, 1983).…”
Section: Fig 8 the Distal Portion Of Transition Ameloblasts In The mentioning
confidence: 99%